1998
DOI: 10.1111/j.1469-7793.1998.235bi.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A induces recruitment of active Na+,K+‐ATPase units to the plasma membrane of rat proximal convoluted tubule cells

Abstract: The aim of this study was to investigate the mechanism of control of Na+,K+‐ATPase activity by the cAMP‐protein kinase A (PKA) pathway in rat proximal convoluted tubules. For this purpose, we studied the in vitro action of exogenous cAMP (10−3 M dibutyryl‐cAMP (db‐cAMP) or 8‐bromo‐cAMP) and endogenous cAMP (direct activation of adenylyl cyclases by 10−5 M forskolin) on Na+,K+‐ATPase activity and membrane trafficking. PKA activation stimulated both the cation transport and hydrolytic activity of Na+,K+‐ATPase b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 41 publications
6
35
0
Order By: Relevance
“…On the other hand, the cell surface expression of the Na + -pump was not altered by C-peptide, therefore increased Na + ,K + -ATPase V max values relies on an increased turnover rate. In agreement with this observation, cAMP synthesis, which results in stimulation of Na + ,K + -ATPase activity through an increase of Na + ,K + -ATPase cell surface expression, was not altered by C-peptide [21,33].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…On the other hand, the cell surface expression of the Na + -pump was not altered by C-peptide, therefore increased Na + ,K + -ATPase V max values relies on an increased turnover rate. In agreement with this observation, cAMP synthesis, which results in stimulation of Na + ,K + -ATPase activity through an increase of Na + ,K + -ATPase cell surface expression, was not altered by C-peptide [21,33].…”
Section: Discussionsupporting
confidence: 71%
“…Phosphorylation of the catalytic α-subunit was assessed by Na + ,K-ATPase immunoprecipitation after 32 P labelling of the α-subunit, as described elsewhere [21]. Outer medullary tubule suspensions were preincubated at 30°C for 2 h in oxygenated solution containing 37.10 Bq/µl [ 32 P]-orthophosphoric acid and then incubated with or without drugs and/or hormones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The action of these networks ultimately results in activation of protein kinases and phosphorylation of the Na ϩ ,K ϩ -ATPase catalytic ␣-subunit (Therien and Blostein, 2000). Depending on the type and isoform of the kinase their action could lead to a decrease or increase in cell Na ϩ ,K ϩ -ATPase activity (Carranza et al, 1998;Efendiev et al, 1999Efendiev et al, , 2000Ridge et al, 2002). However, phosphorylation may not affect the intrinsic properties of the Na ϩ ,K ϩ -ATPase (i.e., catalytic activity) but their subcellular distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This report demonstrated that the functional coupling of CaN and PKA modulated Ca 2+ release in ventricular myocytes (Santana et al, 2002). It has also been demonstrated that Na + -K + www.intechopen.com pump at the basolateral membrane of kidney tubular epithelia was inhibited by CyA (Tumlin & Sands, 1993) and stimulated by PKA (Carranza et al, 1998). On the other hand, a cardiac Na + /Ca 2+ exchanger was reported to be regulated by CaN and PKC (Shigekawa et al, 2007).…”
Section: +mentioning
confidence: 86%